How Do Offline Brand Community Sustain Customer Retention Beyond Transactional Loyalty? - Regina Dinanti Widodo; A.A. Ngr. Oka Suryadinatha Gorda; Ngurah Keshawa Satya Santiarsa (AIBPM Publisher, 2026)
As markets become increasingly saturated and consumers engage in multi-brand usage, transactional explanations of customer retention are becoming less sufficient, particularly in the beauty industry where consumer engagement is strongly influenced by social interaction and identity formation. This study aims to examine how customer retention intention is socially constructed within an offline brand-initiated community by exploring Wardah Beauty Circle Denpasar in Indonesia. Using a qualitative approach through in-depth interviews, participant observation, and documentation, this study investigates how members experience and interpret community participation within a culturally plural context. The findings reveal that customer retention intention emerges as a relational process shaped by emotional safety, identity co-construction, everyday relational interaction, and the negotiation of social tensions and product preference differences. Rather than being driven solely by repeated purchasing behavior, retention reflects relational continuity grounded in emotional attachment and a sense of belonging within the community. The study concludes that offline brand communities can strengthen long-term consumer–brand relationships by fostering emotionally supportive and interaction-rich environments that encourage identity-based belonging beyond conventional repeat-purchase strategies.